2019
DOI: 10.1038/s41598-019-49936-x
|View full text |Cite
|
Sign up to set email alerts
|

Cold exposure induces dynamic, heterogeneous alterations in human brown adipose tissue lipid content

Abstract: Brown adipose tissue undergoes a dynamic, heterogeneous response to cold exposure that can include the simultaneous synthesis, uptake, and oxidation of fatty acids. The purpose of this work was to quantify these changes in brown adipose tissue lipid content (fat-signal fraction (FSF)) using fat-water magnetic resonance imaging during individualized cooling to 3 °C above a participant’s shiver threshold. Eight healthy men completed familiarization, perception-based cooling, and MRI-cooling visits. FSF maps of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 70 publications
7
43
1
Order By: Relevance
“…From this perspective, the range where FF is higher than 70% has previously been assumed to be above the BAT threshold (52). For this reason, we found it remarkable that, in our results, these high-lipid areas of the supraclavicular adipose depot actually showed the largest decrease in lipid and energy content after cold exposure, which is in agreement with recent findings (25). These data suggest that, in fact, one should not use 70% as an upper threshold, and voxels showing up to 100% FF should be used in the analysis [e.g., as performed in (22,53)].…”
Section: The Upper Ff Threshold Range For Bat Ff Analysissupporting
confidence: 93%
See 4 more Smart Citations
“…From this perspective, the range where FF is higher than 70% has previously been assumed to be above the BAT threshold (52). For this reason, we found it remarkable that, in our results, these high-lipid areas of the supraclavicular adipose depot actually showed the largest decrease in lipid and energy content after cold exposure, which is in agreement with recent findings (25). These data suggest that, in fact, one should not use 70% as an upper threshold, and voxels showing up to 100% FF should be used in the analysis [e.g., as performed in (22,53)].…”
Section: The Upper Ff Threshold Range For Bat Ff Analysissupporting
confidence: 93%
“…Both the global and local analyses showed that changes occurred across the entire baseline FF range (30-100%), with the greatest apparent FF decrease when using a 34-100% FF range. The largest FF decrease we observed (i.e., 3.5%) is in the range of values reported in literature (19,21,23), but also much smaller (22) and larger decreases (25) have been reported. This could be due to the use of different thresholds, but also differences in the cooling protocols can play an important role (54,55).…”
Section: The Lower Ff Threshold Range For Bat Analyses Of Ff and Volumesupporting
confidence: 74%
See 3 more Smart Citations